VD_FINDINFO Jug / 2020 / 118 vom 25. Januar 2021 - VD Tribunal cantonal (2021)
RESPONSABILITÉ DÉLICTUELLE, MONNAIE DU PAYS, CONCLUSIONS, ASSOCIATION, DÉCISIONDROIT PRIVÉ | 41 CO, 84 CO, 3 CPC, 155 LDIP